DESCRIPTION OF CHARACTER TRAITS AND CRITERIA - Ismailova Shahlo Valijonovna (Journals Park Publishing, 2024)
In this article, the socialization of a person, definitions of character, character types, types, as well as the criteria of specific characteristics of social relations, emotional aspects of character, intellectual aspects of character.
Keywords: Personality, character, society, socialization, behavior, methods, psychology, pedagogy, values, courage, conscientiousness, sincerity, honesty, goodness, kindness, demandingness, arrogance, thoroughness, frugality and in others, negative qualities - selfishness, avarice.